2012
DOI: 10.1021/cs2005482
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis Science of Bulk Mixed Oxides

Abstract: Bulk mixed oxide catalysts are widely used for various applications (selective oxidation catalysts, electrocatalysts for solid oxide fuel cells, and solid oxide electrolyzers for the production of hydrogen), but fundamental understanding of their structure–performance relationships have lagged in the literature. The absence of suitable surface composition and surface structural characterization techniques and methods to determine the number of catalytic active sites, with the latter needed for determination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
129
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(134 citation statements)
references
References 128 publications
4
129
0
1
Order By: Relevance
“…At the lower TF values methanol was converted to dimethyl ether -DME-and only traces of COx, whereas formaldehyde -FA-was not detected. This stresses the strong acid properties of h-WOx, particularly of the Brɸnsted type [2,3,21,22]. Indeed, strong acid sites hamper the desorption of the adsorbed methoxy intermediate, favoring the molecular encounter with a second molecule of ethanol to form DME, as reported previously [2].…”
Section: Methanol and Glycerol Conversion Under Aerobic Conditionssupporting
confidence: 82%
See 1 more Smart Citation
“…At the lower TF values methanol was converted to dimethyl ether -DME-and only traces of COx, whereas formaldehyde -FA-was not detected. This stresses the strong acid properties of h-WOx, particularly of the Brɸnsted type [2,3,21,22]. Indeed, strong acid sites hamper the desorption of the adsorbed methoxy intermediate, favoring the molecular encounter with a second molecule of ethanol to form DME, as reported previously [2].…”
Section: Methanol and Glycerol Conversion Under Aerobic Conditionssupporting
confidence: 82%
“…Promoted mixed metal oxides bronzes have attracted the attention in the last years since they are effective catalysts in acid and oxidation reaction [1][2][3][4]. As suggested recently, redox and acid-base properties of metal oxides can be strongly changed by tailoring composition and catalyst preparation procedure which determines not only crystal sizes but also the local structure and the electronic/catalytic properties [3].…”
Section: Introductionmentioning
confidence: 99%
“…The catalysts primarily give rise to HCHO, which reflects the dominance of the redox sites on its surface. The decomposition Tp value of the surface methoxide species is directly related to their thermal stability [19]. As shown in Fig.…”
Section: Ch 3 Oh-tpsrmentioning
confidence: 99%
“…Cobalt oxide exhibits weak oxygen bond strength and high turnover frequency for redox reaction [23,24]. Liotta et al reported that the morphological and redox properties of cobalt cerium mixed oxides are strongly dependent on the Co/Ce ratio for methane combustion [25].…”
Section: Introductionmentioning
confidence: 99%